2022
DOI: 10.1039/d2fo03366f
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine restriction improves gut microbiota composition and prevents cognitive impairment ind-galactose-induced aging mice

Abstract: Dietary methionine restriction (MR) has been shown to delay aging and ameliorate age-related cognitive impairments. We hypothesized that changes in the gut microbiota may mediate these effects. To test this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…Previous researches in mice and humans suggested that TMAO production was dependent on variability of the gut microbiota species [ 6 , 47 ]. Of note MR was reported to improve gut microbiota composition in normal, HFD, and aging mice [ 28 , 29 , 40 , 48 ]. Therefore, MR may decrease plasma TMAO levels not by altering the hepatic expression of FMO3 but through decreasing intestinal TMA production via manipulating the gut microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches in mice and humans suggested that TMAO production was dependent on variability of the gut microbiota species [ 6 , 47 ]. Of note MR was reported to improve gut microbiota composition in normal, HFD, and aging mice [ 28 , 29 , 40 , 48 ]. Therefore, MR may decrease plasma TMAO levels not by altering the hepatic expression of FMO3 but through decreasing intestinal TMA production via manipulating the gut microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome plays a crucial role in the intricate relationship between inflammaging, cellular senescence, and aging. Dietary interventions aimed at remodeling the microbiome have the potential to mitigate age-related complications in the gut ( 50 ). Cyclin-dependent kinase inhibitors p16 and p21 serve as valuable markers for cellular senescence, with their levels rising in tandem with the aging process ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential role of these microbiota in FGR still needs further investigation. Dietary supplementation of methionine increased the abundance of intestinal Tyzzerella and production of SCFA, alleviating oxidative stress and inflammatory responses in the hippocampus of d-galactose-induced aging mice [ 44 ]. A small randomized controlled trial demonstrated that supplementation with probiotics for two weeks after birth in newborns born at 35 weeks of gestation and who underwent one or more gastrointestinal surgeries resulted in significantly higher relative abundance of nonpathogenic gut bacteria ( Lactobacillaceae ) compared to infants receiving a placebo [ 45 ].…”
Section: Discussionmentioning
confidence: 99%